Synthesis and Optical properties of New Perylene Derivatives - Galabe, Emile Muah (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Versatile substituents of perylene chrmophores creates higher absorptions in visible region of absorption spectrum and also exhibits higher coefficients of molar extinction. Furthermore, they have the ability to emit light of almost unitary which signifies higher fluorescence quantum yields. Perylene dyes acts a major role in dye sensitized solar cells due to the presence of four carbonyl groups in its core which creates ease of accepting an electron. In this research, N,N′-Bis(3,3,5,5-tetramethyl-4-piperidinyl)-3,4,9,10-perylenebis (dicarboximide) (PPDI) and N-(3,3,5,5-tetramethyl-4-piperidinyl)-3,4,9,10-perylenetetracarboxylic-3,4-anhydride-9,10-imide (PPMI) were sensitized and comparison of their photophysical properties were carried out. FTIR spectroscopy was used to characterize the compounds and their photophysical properties analyzed via absorption and emission spectroscopy. All the perylene dyes synthesized showed very high molar absorptivity with the highest being 152000 M-1cm-1 obtained from PPMI. PPMI absorption spectrum shows a 4 nm blue shift in a polar aprotic solvent as a result of increased level of polarity and the stabilization of PPMI energy levels it induces on the structure. Keywords: Perylene diimide, perylene tetracarboxylic acid, perylene monoimde, perylene carboxylic acid monoimide.

ÖZ : Çok Yönlü atomuna no oluşturur perylene chrmophores emilimler daha yüksek görünen bölge absorpsiyon spektrumu ve olduysa da daha yüksek varyasyon katsayıları molar sönme. Ayrıca, ışık yaydığından yeteneğine sahip olan hemen hemen devletin üniter anlamına gelmektedir uygulandığında flüoresans üreten kendinden aydınlatmalı kuvantum verimleri daha yüksek. Görevi görür Perylene boyalar önemli bir rol boya pozlandırmadan güneş enerjisi hücreleri bulunması nedeniyle dört carbonyl grubu oluşturan, temel kabul kolaylığı bir elektron. Bu araştırma, N, N' -Bis(3,3,5,5-tetramethyl-4-piperidinyl)-3,4,9,10-perylenebis (dicarboximide) (PPDI) ve N- (3,3,5,5-tetramethyl-4-piperidinyl)-3,4,9,10-perylenetetracarboxylic-3,4-anhidrit-9,10-imide (PPMI) pozlandırmadan ve karşılaştırma, photophysical özellikleri gerçekleştirildi. FTIR spektroskopi, karakterize etmek için kullanılan bileşikler ve onların photophysical özellikleri üzerinden analiz emilim ve emisyon spektroskopi. Gösterdi Tüm perylene boyalar sentezlenmiş çok yüksek molar absorptivity olan en yüksek 152000 M-1cm-1 elde PPMI. PPMI absorpsiyon spektrumu 4 nm mavi gösterir vardiya kutup ayısı aprotic solvent sonuç olarak artan düzeyde polarite ve stabilizasyonu PPMI enerji seviyelerine yankılanmaya neden olur. Anahtar Sözcükler: Perylene diimide, perylene tetracarboxylic asit, perylene monoimde, perylene carboxylic asit monoimide.
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2014. Supervisor: Prof. Dr. Huriye İcil.
Keywords: Chemistry; Dyes (Chemistry); Perylene Dyes; Photochemistry; Perylene diimide; perylene tetracarboxylic acid; perylene monoimde; perylene carboxylic acid monoimide